Application of force prediction to rotating equipment using pseudo-inverse techniques - Stansloski, Mitchell, author; Smith, Fred W., advisor; Wilbur, Paul, committee member; Willson, Bryan, committee member; Bienkiewicz, Bogusz, committee member (Colorado State University. Libraries, 2010)
Extracting forcing functions for the purposes of signature analysis and load computation will improve root cause analysis on costly failures of rotating industrial equipment. By utilizing vibration signature response data and frequency response functions, both traditional troubleshooting technologies, the inverse method of force prediction has a high likelihood of becoming a useful force prediction tool to industrial maintenance staff. In prior research, force prediction using inverse methods has been studied and proven valid for a number of uni-axial structural configurations and external dynamic loadings. Minimal previously published studies have addressed computing internal forcing functions within rotating systems using these inverse techniques with experimental transfer functions. In this research, proof of concept is first obtained by applying the inverse method to a closed form solution of a rotating rigid shaft and disk assembly. Then, the method is validated with experimental data taken from a flexible rotating shaft system. Once validation is obtained, various rotating shaft speeds and loadings are studied. It is shown that this method can be an effective and accurate tool for root cause analysis in rotating industrial machinery.
Covers not scanned.
Keywords: Machinery -- Vibration; Electric machinery -- Rotors; Pseudoinverses